floprovides
floprovides
01-09-2017
Mathematics
contestada
g(x)= 3x − 3; Find g(−6)
Respuesta :
wikk
wikk
01-09-2017
g(x)= 3x − 3
g(−6)
g(-6) = 3(-6) - 3
g(-6) = -18 - 3
g(-6) = -21
The answer is -21.
Answer Link
choixongdong
choixongdong
01-09-2017
g(−6) =
3(-6) − 3 = -18 - 3 = -21
answer
g(−6) = -21
Answer Link
VER TODAS LAS RESPUESTAS ( 95+ )
Otras preguntas
How did the Declaration of Independence change the nature of the American Revolution?
a soccer team played 160 games and won 65% of them. how many did they win?
Simplify (7-5i)(-3+9i)-(5+6i)^2
how is the expression of sex linked genes both similar to and different from the expression of autosomal genes?
How did the depression affect women and children?
how is the expression of sex linked genes both similar to and different from the expression of autosomal genes?
The gases in the air attracted to earth by gravity form layers called the ____
Why were the 1920's considered the best and worst of times?
sam cut a pie into equal parts.There are 3 slices left.The angle measures for 3 slices is 72.how many slices did he cut?
What is the main religion of Latin america